Preparation and performance of Sn-based composite solder joints by solid-liquid low-temperature solder bonding technology - Xuefeng Wu; Lingyao Sun; Yingxia Liu; Ziting Ye; Xiuchen Zhao; Ying Liu (Journal of Materials Research and Technology, 2023)
In the era of big data, the advantages of 3D packaging are becoming increasingly significant. In addition, the mismatch between the coefficient of thermal expansion (CTE) of the PCB and BGA components leads to dynamic warpage of the system, and the expansion and innovation of low-temperature soldering have been a new trend. We developed a fully mixed solder joint of a SAC305(Sn-3.0Ag-0.5Cu wt.%) solder ball and Sn–58Bi(wt.%) solder paste by solid-liquid low-temperature solder bonding technology. The mixing degree and diffusion process of the two were calculated and simulated by mathematical calculation and COMSOL Multiphysics. The results show that a completely mixed solder joint can be obtained after reflow at 210 °C for 5 min. The average shear strength of the composite solder joints was 63.68 ± 1.12 MPa, which was about twice that of the single SAC305 and Sn58Bi solder joints, and the shear fracture was a composite mode of brittle and ductile fracture, which appeared in the IMC and the solder, respectively. After complete mixing, the solder wettability angle was less than 26.68°, with outstanding wetting properties. No phase transition occurred after aging, the distribution of each phase remained uniform, and no enrichment of the brittle phase was observed at the interface. The shear strength decreased slightly with aging time, and the reduction value was less than 10 MPa, which has good reliability.